Marcas de autoria no gênero acadêmico dissertação de mestrado - Munhoz, Maria Vitória Martini Paula Garcia (2014)
This dissertation is inserted into the line of research Text and discourse in the oral and written modalities and has as its theme authorship in academic texts. Therefore aims to analyze, in an interactional socio-cognitive perspective and in the context of Textual Linguistics and Textual Analysis of the Discourses, the constitution of the author while producing the chapter of theoretical foundation for her master s degree dissertation, in order to understand if she expresses authorship in her textual production. The overall objective of this work is to study authorship in master s degree dissertations and the specific objectives are to identify, describe, analyze and interpret the linguistic marks that in the opinion of Adam (2011) and Koch, Bentes and Cavalcante (2008), the writer uses in her written production to reveal authorship. With regard to the methodological procedures, we adopted a qualitative research method and a document analysis. The data that formed the corpus of the analysis consisted of excerpts of ten dissertations defended in the year 2012 at the Pontifícia Universidade Católica of São Paulo. The results showed that the linguistic units comprised by the seventh textual level (N7) of Adam (2011) analysis and the concept of explicit intertextuality , from Koch, Bentes and Cavalcante (2008) allow the search of linguistic marks that demonstrate the compromise of the author with the propositional content enunciated. Additionally, in the analyzed dissertations, the authors sough to assume authorship while writing theirs texts, although, at times, the degree of commitment has been shown greater or minor